Refugee Migration and the Politics of Redistribution: Do Supply and Demand Meet? - Matakos Konstantinos; Savolainen Riikka; Tukiainen Janne (Aboa Centre for Economics, 2025)
Voter demand for less redistribution in the face of mass migration maps into actual outcomes insofar as politicians supplying these policies respond to it. We study whether establishing new asylum-seeker centers influences redistributive outcomes in Finnish local elections - a country where municipalities have a significant control over fiscal policies. The sudden and unprecedentedly large inflow of asylum-seekers in the fall 2015 and the resulting establishment of asylum centers allows for a difference-in-differences design. We examine simultaneously supply and demand for redistribution by focusing both on candidates’ policy positions and also voters’ preferences. On the supply side, we find that, on average, candidates do not respond to the presence of refugees by adopting anti-redistributive positions. Our estimates are precise enough to rule out even fairly small effects. In contrast, on the demand side, there is evidence of various voter responses against redistribution (and in favor of the anti-immigration party), on average suggesting that representative democracy filters the mapping of voter preferences on policy outcomes. But this political disequilibrium comes at the price of a populist backlash : we find decreased support for insider elite candidates. We probe the mechanism behind the backlash: in the localities more intensely exposed to refugee migration, we observe also a supply-side response (candidates oppose redistribution) while a demand response is less heterogeneous. In the municipalities where the gap between demand and supply is wider also the backlash is larger.